Marketing Orientation Led by Consumer Motivations Towards Agribased Products : An Evidence from Udupi District in India - Baliga, Vikram; Santhosha Shetty, G.; Shenoy, Sandeep (Indian Journal of Marketing, 2020)
In this paper, we analyzed consumer motivations towards locally grown fruits and vegetables in the city of Udupi, Karnataka (India). A survey was conducted using mix method (both qualitative and quantitative design) to elicit responses from consumer households of the region. Deductive study design was used to identify concepts and codes of research interest from existing literature and pilot study was conducted to induce new concepts and codes. Further, factor analysis (principal component method) was performed to identify and retain key elements defining consumer motivations. The results indicated that sensory appeal, customer engagement, utility factors, and convenience in shopping were key motivators that influenced consumers’ preferences towards locally grown fruits and vegetables. The results were used to develop a stage wise conceptual framework on consumer motivations towards F&V. The study suggested a marketing orientation plan to promote the consumption of fresh fruits & vegetables and its value added products. The marketing strategies can be adopted by horticulture promoting agencies, policy makers, and marketers to design mass marketing campaigns and awareness programs to promote agribusiness.